Applications of 3D printing in cancer. Issue 3 (14th August 2018) - Serrano, Dolores R; Terres, Maria C; Lalatsa, Aikaterini
The tumor heterogeneity and interindividual variability is a major problem when treating cancer as every patient responds in a different way to the current drug therapies. 3D printing is a tool that can hamper the issues faced in cancer patients allowing for individualization of treatment by the production of in vitro models with microenvironments mimicking more closely real cancer conditions facilitating complex therapies. Further improvements are required, for example the development of biocompatible bioinks or need for vascularization. The journey from bench to bedside is challenging from the regulatory point of view where the establishment of manufacturing guidelines, quality systems and safety of use and administration of personalized medicines remains unclear. This review will provide an insight into the major applications of 3D printing in cancer both in the development of in vitro cancer models as well as personalized medicines for cancer patients focused on hydrogels and therapeutic implants.